Analysis of Pancasila Student Profile of Mutual Cooperation Elements Through the Market Day Project in Grade IV Elementary School Students - Rahmawati, Dwi; Saputro, Bagus Ardi; Utami, Sari; Roshayanti, Fenny (DIDAKTIKA, 2024)
This study aims to analyze the implementation of the Pancasila Student Profile, specifically the element of cooperation (gotong royong), through the Market Day project among 4th-grade students in elementary school. The research method used is qualitative and data collection techniques are used including observation, interviews, and documentation. The results of the study show that the Market Day project can foster the element of cooperation among 4th-grade elementary school students. This is evidenced by the students' enthusiasm in participating in the project, helping each other in completing tasks, and showing a sense of responsibility towards their group. The Market Day project provides students with the opportunity to learn to work together, respect each other, and solve problems collectively. Additionally, this project helps students develop entrepreneurial skills such as creativity, communication, and negotiation. Based on the results, it is concluded that the Market Day project is an effective teaching method to foster the element of cooperation among 4th-grade elementary school students. Teachers need to implement the Market Day project continuously and integrate it with the school curriculum to achieve optimal learning objectives.